Linkage analysis of chromosome 17q markers and breast-ovarian cancer in Icelandic families, and possible relationship to prostatic cancer - Arason, A; Barkardottir, R B; Egilsson, V (University of Chicago Press, 2011)
To access publisher full text version of this article. Please click on the hyperlink in Additional Links field Seven families, selected for breast cancer segregation, have been analyzed for chromosome 17q12-q23 linkage to breast and ovarian cancer. In two of them, linkage is seen with most markers tested, increasing toward the most proximal region, but without informative recombinations above NM23. In the remaining families, no linkage is observed. Families with 17q linkage are not easily distinguished by clinical characteristics such as early onset (mean age at diagnosis < or = 45 years) or organs involved. In fact, the family with the highest lod scores (> or = 2.3) belongs to the "later onset" (> 45 years) category of families. Interestingly, prostatic cancer is the most frequent malignancy, after breast cancer, in the families that we studied (13 cases total, all metastasizing) and is especially prevalent in males presumed to carry the trait. Of 16 paternal carriers, 7 (44%) had developed prostatic cancer. Haplotype analysis in families with 17q linkage reveals two further prostatic cases as potential carriers. We propose that breast cancer genes may predispose to prostatic cancer in male carriers.